Plant Regeneration in Rauvolfia serpentina (L.) Benth via Organogenic Mode - M. K. Tripathi; G. Tiwari; Sushma Tiwari; Niraj Tripathi; Nishi Mishra; Yashi Singh Tomar; D. S. Uikey; Sharad Tiwari (Research Aspects in Biological Science Vol. 7, 2022)
An effectual protocol for rapid propagation of Rauvolfia serpentina has been standardized in present investigation. Leaf discs and nodal segments were inoculated on MS medium supplemented with diverse auxins and cytokinins in variable concentrations as individual along with in different amalgamations. to recognize the most responding explants, plant growth regulators and calculate their optimum concentrations and other culture conditions revealing in vitro morphogenesis tracked by plantlet regeneration in higher frequencies by means of nodal segments and leaf discs culture of locally adapted cultivar. For nodal segment culture, basal MS media amended with 2, 4-D/ NAA at the concentration of 2.0 mgl-1as alone or in association with 0.5mgl-1 TDZ were evidenced meaningly better for callus initiation. However, higher shoot proliferating competence, numbers of shoots per explant with maximum length were recognized on inoculation media reinvigorated with TDZ in the range of 0.2-0.5 mgl-1 as sole as well as in association with 0.5mgl-1NAA (more than 92% nodal segments initiated shoots, >10.5 shoots/explant and mean shoot length>3.85 cm). Nevertheless, for inoculated leaf disc, maximum callus and morphogenic callus formation along with plantlet regeneration were investigated on culture media supplemented with 2.0 mgl-1 auxins: 2,4-D and/or NAA in amalgamation with 0.5mgl-1of a cytokinin BA and/or TDZ (more than 76% leaf discs initiated morphogenic calli with >80% regeneration frequencies). Rooting medium MS modified with 0.1 mgl-1IBA demonstrated a higher in vitro rooting response (root proliferating efficiency, number of roots with higher length).